Analisis Kinerja Keuangan Perusahaan Perkebunan Kelapa Sawit: PT. Sinar Mas Agro Resources and Technology Tbk. (SMART) - Hermiandra, Dennis Wara; Relawati, Rahayu (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Around 85% up to 90% of the world's total palm oil production is produced from Indonesia and Malaysia. PT. Sinar Mas Agro Resources and Technology Tbk (SMART) is a public company that has been listed on the IDX since 1992. The objectives of this study are (1) Describe the brief profile of PT. SMART Tbk.; (2) Analyze the development of financial performance; and (3) Analyze the financial health of the company. The study analyzed descriptive and financial ratios.  The results of the study showthat palm oil productivity at PT. SMART Tbk. amounted to 5.5 tons/ha/year, with total CPO and kernel production of 3.8 million tons or around 613.4 thousand tons/year. The trade conflict between the United States and China and non-tariff barriers from the European Union are one of the factors causing the decline in CPO production. PT. SMART Tbk.  Net sales increased from 2017 to 2021 and reached a record high of IDR 57 trillion in 2021.  Netsales decreased in 2019, but there was an increase in net profit to Rp 898.6 billion.  Average NPM value of 3.24/year and average ROI value of 4.20/year; average CR value of 1.33/year and average QR value of 0.86/year; while the average DAR value is 61.04/year and the average DER value is 158.03/year.